Pengembangan Ekonomi Hijau Yang Didasarkan Pada Maqashid Syari'ah Dalam Pembangunan Berkelanjutan - Hapisuddin, Hapisuddin; Sari Lubis, Delima; Batubara, Damri (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
Economists rely on the economic system for making policies; contohnya, the Green Economy, which is based on Maqashid Shari'ah, is a goal based on Islamic teachings to achieve prosperity, and the Green Economy itself is a concept that produces welfare in the long term. The research examines how the concepts of Green Economy and Maqashid Shari'ah become supporting instruments and their role in enhancing the welfare of sustainable development in Indonesia. Untuk menginterpretasikan temuan penelitian sebelumnya, ini adalah penelitian kualitatif yang menggunakan analisis deskriptif. Data sumber adalah sumber tambahan dari penelitian lembaga pustaka dalam bentuk buku dan lainnya. The results obtained are that Indonesia is very suitable to implement the concept of Green Economy based on Maqashid Shari'ah in an effort to prosper the community without any act of exploitation of natural resources that causes social inequality.